STANDARD OPERATING PROCEDURE (SOP) PENERIMAAN TAMU (Studi Kasus Politeknik Negeri Bengkalis) - M Hamidi; Wan Junita Raflah (Inovbiz: Jurnal Inovasi Bisnis, 2018)
This research aims to design and create a Standard Operating Procedure SOP or reception at checkpoints guards of State Polytechnic. The method used is descriptive qualitative, method of data collection in the form of observation, the study of the literature and interviews. The results of this research is the SOP or Standard Operating Procedure reception at State Polytechnic Bengkalis which can be used by default.  SOP type created is formats technical an form of format combinations.